Discourses, Dialogue and Diversity in Biographical Research An Ecology of Life and Learning - Bainbridge, Alan; Formenti, Laura; West, Linden (Research on the Education and Learning of Adults, 2021)
This book explores how narratives are deeply embodied, engaging heart, soul, as well as mind, through varying adult learner perspectives. Biographical research is not an isolated, individual, solipsistic endeavor but shaped by larger ecological interactions - in families, schools, universities, communities, societies, and networks - that can create or destroy hope. Telling or listening to life stories celebrates complexity, messiness, and the rich potential of learning lives. The narratives in this book highlight the rapid disruption of sustainable ecologies, not only 'natural', physical, and biological, but also psychological, economic, relational, political, educational, cultural, and ethical. Yet, despite living in a precarious, and often frightening, liquid world, biographical research can both chronicle and illuminate how resources of hope are created in deeper, aesthetically satisfying ways. Biographical research offers insights, and even signposts, to understand and transcend the darker side of the human condition, alongside its inspirations. Discourses, Dialogue and Diversity in Biographical Research aims to generate insight into people's fears and anxieties but also their capacity to 'keep on keeping on' and to challenge forces that would diminish their and all our humanity. It provides a sustainable approach to creating sufficient hope in individuals and communities by showing how building meaningful dialogue, grounded in social justice, can create good enough experiences of togetherness across difference. The book illuminates what amounts to an ecology of life, learning and human flourishing in a sometimes tortured, fractious, fragmented, and fragile world, yet one still offering rich resources of hope. Readership: All those interested in using narrative, life history and biographical research methods to explore the education of adults particularly in relation to building meaningful dialogue, grounded in social justice to create good enough experiences of togetherness across difference.